THE INFLUENCE OF INTEGRATING AL-QUR'AN VALUES IN THE CURRICULUM ON THE FORMATION OF ANTI-RADICALISM CHARACTER AMONG STUDENTS - Umi Sa'adah; Agus Nur Qowim (STAI Asy-Syukriyyah, 2026)
This study investigates the influence of integrating Al-Qur'an values in the school curriculum on the formation of anti-radicalism character among students in Islamic educational institutions in Indonesia. Using a quantitative research approach with a survey methodology, data were collected from 320 students across five Islamic junior and senior high schools in Jakarta and its surrounding areas. Instruments included a validated questionnaire measuring the level of Al-Qur'an values integration (as the independent variable) and the anti-radicalism character formation scale (as the dependent variable). Data analysis employed Pearson correlation, simple linear regression, and multiple regression techniques. The results demonstrate a significant positive influence of Al-Qur'an values integration on anti-radicalism character formation, with a regression coefficient (β = 0.612, p < 0.01) and an R² value of 0.487, indicating that 48.7% of the variance in anti-radicalism character is explained by Al-Qur'an curriculum integration. The findings affirm that dimensions such as tawassuth (moderation), tasamuh (tolerance), tawazun (balance), and i'tidal (fairness) embedded in the curriculum significantly contribute to shaping students' resistance to radical ideologies. This research contributes to the theoretical and practical discourse on curriculum-based character education in countering radicalism within Islamic educational institutions.